2006
DOI: 10.1177/106689690601400205
|View full text |Cite
|
Sign up to set email alerts
|

Colonic and Duodenal Flat Adenomas in Children with Classical Familial Adenomatous Polyposis

Abstract: Flat adenomas of the colon and duodenum have been described as associating with familial adenomatous polyposis (FAP), its attenuated variant, and the so-called hereditary nonpolyposis colorectal cancer. There seem to be no report on the occurrence of flat adenomas in pediatric patients with family history of FAP. We are reporting 4 children from 2 cancer-prone families in whom colonic and duodenal moderately dysplastic flat adenomas were found. Gastrointestinal endoscopy and biopsies were performed in 3 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…29 The polyp size and contour observed endoscopically in classic FAP is a small raised lesion with a rounded contour; in contrast, polyps in attenuated FAP although also small (<1 cm) are flat in appearance, showing only minimal mucosal elevation. 30 Unicryptal adenoma is the pathognomonic lesion in FAP, originally described microscopically but which can now be identified by chromoendoscopy. 31 It has been reported that small polyps (<3 mm in size) are not observed after barium enema, resulting in underestimation of the number of polyps.…”
Section: Associated Common Intestinal Neoplasmsmentioning
confidence: 99%
“…29 The polyp size and contour observed endoscopically in classic FAP is a small raised lesion with a rounded contour; in contrast, polyps in attenuated FAP although also small (<1 cm) are flat in appearance, showing only minimal mucosal elevation. 30 Unicryptal adenoma is the pathognomonic lesion in FAP, originally described microscopically but which can now be identified by chromoendoscopy. 31 It has been reported that small polyps (<3 mm in size) are not observed after barium enema, resulting in underestimation of the number of polyps.…”
Section: Associated Common Intestinal Neoplasmsmentioning
confidence: 99%
“…Our finding of flat adenomas in children with FAP is also in the same line of reasoning. 8 Moreover, ACF have been proposed to act as traps of dietary carcinogens. If so, the larger the number of ACF, the greater is the possibility of developing additional mutations leading to tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Tubular-villous and villous adenomas are also quite frequent [30]. Moreover, intestinal polyps can also occur as flat tubular polyps [31]. One of the typical features of polyposis is a severe phenotype in which the number of polyps exceed one thousand [32].…”
Section: Introductionmentioning
confidence: 99%